An Overview On Tuberculosis And Advanced Diagnostic Methodlogy (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2024)
Tuberculosis (TB), is caused by Mycobacterium tuberculosis complex, is one of the ancient diseases which affect more likely in humans. Tuberculosis is a major cause of morbidity and mortality worldwide. It is determined that 25% of world's population are infected with Mycobacterium tuberculosis, with a 5-10% lifetime risk of progression into Tuberculosis disease. Tuberculosis is highly widespread among the low socioeconomic section of the population and marginalized sections of the society. Methods based on the detection of Mycobacterium tuberculosis (Mtb) are inadequate sensitive, methods based on the identifying of Mtb-specific immune responses cannot always differ from active disease from latent infection, and few of the serological markers of infection with Mtb are insufficiently specific to differentiate tuberculosis from further inflammatory diseases. New tools based on technologies such as mass spectrometry, high-throughput sequencing, and artificial intelligence have the potential to solve this tight corner. The aim of this review was to provide an updated overview of optimize classical diagnostic methods, as well as new molecular and other techniques, for appropriate diagnosis of patients with tuberculosis infection. Treatment regimen for sensitive active TB and latent TB was provided.